Serial anaerobic digestion improves protein degradation and biogas production from mixed food waste. (June 2022) - Perman, Ebba; Schnürer, Anna; Björn, Annika; Moestedt, Jan
Abstract: Optimization of the biogas generation process is important to achieve efficient degradation and high methane yield, and to reduce methane emissions from the digestate. In this study, serial digester systems with two or three biogas reactors were compared with a single reactor, with the aim of improving degree of degradation and methane yield from food waste and assessing adaptation of microbial communities to different reactor steps. All systems had the same total organic load (2.4 g VS/(L d)) and hydraulic retention time (55 days). Serial systems increased methane yield by >5% compared with the single reactor, with the majority of the methane being obtained from the first-step reactors. Improved protein degradation was also obtained in serial systems, with >20% lower outgoing protein concentration compared with the single reactor and increasing NH4 + -N concentration with every reactor step. This resulted in separation of high ammonia (>384 mg NH3 -N/L) levels from the main methane production, reducing the risk of methanogen inhibition. Methanosarcina dominated the methanogenic community in all reactors, but increases in the hydrogenotrophic genera Methanoculleus and Methanobacterium were observed at higher ammonia levels. Potential syntrophic acetate-oxidizing bacteria, such as MBA03 and Dethiobacteraceae, followed the same trend as the hydrogenotrophic methanogens. Phylum Bacteroidota family Paludibacteraceae was highly abundant in the first steps and then decreased abruptly, potentially linked to an observed decrease in degradation in the last-step reactors. Nevertheless, the results indicated a trend of increasing relative abundance of the potentially proteolytic genera Proteiniphilum and Fastidiosipila with successive reactor steps. Graphical abstract: Image 1 Highlights: Serial anaerobic digestion increased methane yield from food waste by >5%. VS reduction was significantly greater in serial digestion than in a single reactor. Protein degradation was >20% more efficient in serial digestion systems. A serial digester setup lowered residual methane production from digestate. Microbial community structure changed over reactor steps in serial digester systems.